Hope Vale Council news : from dreaming to reality. ([Hopevale, Queensland] : Hope Vale Aboriginal Shire Council, 2018)
Hope Vale township is situated 46km north west of Cooktown and is home to thirteen clan groups who mostly speak Guugu Yimithirr and other related languages, as well English. The newsletter covers local and Council news as well as State and Federal decisions affecting the region, local events, and staff profiles.
Title from cover page (viewed on August 18, 2021)
Description based on: 1 August 2018 (2018)
Keywords: Hope Vale Aboriginal Shire (Qld.). -- Council -- Periodicals; Manners and customs; Hope Vale (Qld. : Shire) -- Periodicals; Hope Vale (Qld.) -- Social life and customs -- Periodicals; Electronic journals; Periodicals